2020
DOI: 10.1371/journal.pone.0235378
|View full text |Cite
|
Sign up to set email alerts
|

Ruminative and mood associations for age differences in social and directive reasons to think and talk about life experiences

Abstract: Reminiscing, or thinking and talking about our past experiences, can have mood enhancing effects. Rumination is implicated in reminiscence and yet has been shown to have negative effects on mood, with important differences between age groups. However, age differences in the effects of reminiscing on mood, and particularly the effects of rumination within reminiscence, are less explored. Two different age groups completed self-report measures of the positive directive (planning for present and future behaviors)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…Whereas previous studies have consistently suggested associations between higher ruminative tendencies and psychological health, the magnitude of these associations has been suggested to vary by age and/or cultural background. For example, Ricarte, Ros, Latorre, and Barry [ 62 ] reported that young participants in their twenties are more prone to ruminate than are older participants in their seventies. Regarding cultural differences, Tsai, Chang, Sanna, and Herringshaw [ 63 ] suggested that European Americans high in ruminative tendencies show lower levels of anxiety and depression when happiness is high, whereas Asian-Americans who tend to ruminate show high anxiety and depression regardless of happiness level.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas previous studies have consistently suggested associations between higher ruminative tendencies and psychological health, the magnitude of these associations has been suggested to vary by age and/or cultural background. For example, Ricarte, Ros, Latorre, and Barry [ 62 ] reported that young participants in their twenties are more prone to ruminate than are older participants in their seventies. Regarding cultural differences, Tsai, Chang, Sanna, and Herringshaw [ 63 ] suggested that European Americans high in ruminative tendencies show lower levels of anxiety and depression when happiness is high, whereas Asian-Americans who tend to ruminate show high anxiety and depression regardless of happiness level.…”
Section: Discussionmentioning
confidence: 99%
“…The final multivariate regression model showed that an increase in Bitterness Revival scores yielded a significant increase in depression and loneliness scores. This result could be explained by the fact that when older adults constantly focus on their negative life events and ruminate on painful memories, this could contribute to the development of psychological disturbances 38 . Previous studies 12,16,39 have shown that dwelling on painful memories and unresolved conflicts has various consequences for mental health, namely depression and loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…Loneliness is strongly linked to depression; 38 loneliness might contribute to a person's re‐experiencing unresolved problems and repetitive negative thinking that emerge as depressive symptoms 16 . Preoccupation with a bitter past reflects an inability to fulfil social interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there may be potential differences in either EF or ruminative tendencies between middle adulthood and late adulthood, we include age as a moderator in our analyses. However, we were unable to outline any specific predictions due to the scant research on EF or ruminative differences between middle adulthood and late adulthood; most studies simply compare younger adults with older adults (Ferguson et al, 2021; Ricarte et al, 2020).…”
Section: Limitations Of Previous Studiesmentioning
confidence: 96%